The message the story of Islam - Akkad, Moustapha; Filmco International ([S.l] : Filmco International ; Indonesia : PT Merak Cipta Indo Kreasi (distributor), 1999)
An epic dramatization of the founding of Islam, focusing not on a portrayal of the Prophet Mohammad, but on the action surrounding his activities
Title from title cover
In English with subtitle in Indonesian
Music composed and conducted by Maurice Jarre ; screenplay by H.A.L. Craig ; photographed by Jack Hildyard
Cast: Anthony Quinn, Irene Papas, Michael Ansara, Johnny Sekka, Michael Forest
Keywords: Islam -- Foundation -- Drama; Islam -- Drama